CONCEPT OF CONSTRUCTION OF MEASURING AND CONTROL MODULES FOR CRITICAL INFRASTRUCTURE FACILITIES - KOCHAN, OREST; BYKOVYY, PAVLO; ZASTAVNYY, OLEG; SACHENKO, ANATOLIY; KOCHAN, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article discusses the concept of building intelligent measuring and control modules, which are intended for operation as part of monitoring and control systems of critical infrastructure objects. The difficulty of increasing the reliability of the signals of sensors of physical quantities is that for their traditional metrological verification it is necessary to place their sensitive element in this physical quantity, and the value of this physical quantity must be known with an error smaller than the permissible error of the sensor.The concept of construction of VKM developed in this article assumes that they have a number of properties that are required during operation as part of OKI. The presence of wireless communication and backup power ensures a high level of survivability of the developed VKM, which is an absolutely necessary condition for their sufficient informativeness in the conditions of accidents of various origins and post-accident situations. High informativeness both during normal operation and in such specific conditions is also ensured by the possibility of remote reprogramming. This enables the developed VKM to use various methods of processing the results of current measurements during normal operation, as well as specialized methods of data processing adequate to the emergency situation that has arisen (even urgently developed specifically for the study of some unexpected aspect of the behavior of the OKI in current conditions). At the same time, it is remote reprogramming that allows for arbitrary reconfiguration of the software of the offered VKM without restrictions imposed by various types of operating systems. And the presence of a dedicated reprogramming microcontroller allows you to examine the received software for damage caused by the data exchange process or unauthorized intrusion.
Keywords: measuring and control modules; object of critical infrastructure; reliability of measurements; ADC; Transducer Electronic Data Sheet